Total knee arthroplasty exposures and soft tissue balancing - Insall, John N. ([Philadelphia, Pa.] : J.B. Lippincott Co., 1994)
(Producer) This video presents the latest arthroscopic and joint replacement procedures performed by top orthopaedic surgeons. This six-volume set offers a compelling first hand view of advanced techniques. For each procedure, the surgeons review the rationale, indications and contraindications, surgical exposures and technique and point out how to avoid pitfalls and complications. Innovative technical tips are highlighed throughout. These volumes provide valuable advice and expert consultation as you prepare for your difficult cases
Keywords: Knee joint -- Surgery; Arthroplasty